REVEALING THE SOCIAL LEARNING NEEDS OF COASTAL SCHOOLS BASED ON SWOT ANALYSIS - Shahibah Yuliani; Disman Disman; Enok Maryani; Siti Nurbayani; Eva Precilia Lukman (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
ABSTRACT This study aims to explore the development needs of social learning in coastal schools, with a specific focus on Coastal Junior High Schools in Jakarta amidst various environmental challenges and degradation. The research employs a descriptive qualitative approach, integrating SWOT analysis to identify strengths, weaknesses, opportunities, and threats related to the social learning needs in addressing coastal and marine environmental issues. Data collection involves questionnaires, interviews, and focused group discussions with 29 junior high school educators from coastal areas in Jakarta. The findings reveal the necessity for teachers to develop environmentally based teaching materials, create relevant learning modules, and utilize the environment as a learning resource. Furthermore, teachers require adequate digital skills to effectively support environment-based learning. Emphasizing the importance of contextual learning and placed-based education, the study advocates for creating learning experiences relevant to the context and integrating digital technology to meet the needs and implications of shaping environmentally conscious communities and enhancing the quality of education in coastal schools.Keywords: Coastal Schools, Social Learning, SWOT analysisÂ ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi kebutuhan perkembangan pembelajaran sosial di sekolah pesisir, khususnya fokus pada Sekolah Menegah Pertama Pesisir Jakarta di tengah berbagai tantangan dan degradasi lingkungan. Studi ini menggunakan pendekatan kualitatif deskriptif dengan mengintegrasikan analisis SWOT untuk mengidentifikasi kekuatan, kelemahan, peluang, dan ancaman terkait kebutuhan pembelajaran sosial dalam mengatasi masalah lingkungan pesisir dan laut. Pengumpulan data melibatkan kuesioner, wawancara, dan diskusi kelompok terfokus dengan 29 pendidik sekolah menengah pertama dari daerah pesisir Jakarta. Hasil penelitian mengungkapkan kebutuhan guru untuk mengembangkan bahan pengajaran berbasis lingkungan, menciptakan modul pembelajaran yang relevan, dan memanfaatkan lingkungan sebagai sumber pembelajaran. Selain itu, guru memerlukan keterampilan digital yang memadai untuk mendukung pembelajaran berbasis lingkungan secara efektif. Menegaskan pentingnya pembelajaran kontekstual dan pendidikan berbasis tempat dalam menciptakan pengalaman belajar yang relevan dengan konteks dan mengintegrasikan teknologi digital untuk memenuhi kebutuhan serta berimplikasi membentuk masyarakat yang peduli lingkungan dan meningkatkan kualitas pendidikan di sekolah-sekolah pesisir.Kata kunci: Sekolah pesisir, pembelajaran social, analisis SWOTÂ